Strategi Keberlanjutan Program Pengelolaan Sampah di Hutan Kota Pesanggrahan Sangga Buana - Azillah, Nurul; Rahmawati, Isna (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2024)
ABSTRACTEmpowerment of the Sangga Buana Environmental Farmer Group (KTLH) is carried out through a waste management program that aims to protect nature and the environment. In an empowerment program, sustainability is something that must be considered. The purpose of this research is to find out the sustainability strategy of the waste management program, as well as the driving and inhibiting factors of the waste management program. This research uses qualitative research methods with descriptive research types, data collection techniques using observation interviews, and documentation. Data analysis was carried out by data reduction, data presentation, and verification and conclusion drawing. The results showed that the sustainability strategy of the waste management program can be seen through the strategy of strengthening local institutions, fostering community cadres, and funding sources. Meanwhile, the empowerment of the Sangga Buana Environmental Farmer Group (KTLH) can be seen through environmental, social, and economic sustainability. The sustainability strategy of the waste management program as an empowerment of the Sangga Buana Environmental Farmer Group (KTLH) can be said to be successful, because they has a sustainable source of funding, improves the quality of the environment, and increases the income of group members.Key Word : Empowerment, Farmer Group, Waste Management, Sustainability. ABSTRAKPemberdayaan Kelompok Tani Lingkungan Hidup (KTLH) Sangga Buana dilakukan melalui program pengelolaan sampah yang bertujuan untuk menjaga alam dan lingkungan. Pada suatu program pemberdayaan, keberlanjutan merupakah hal yang harus diperhatikan. Tujuan penelitian ini yaitu untuk mengetahu strategi keberlanjutan program pengelolaan sampah, serta faktor pendorong dan penghambat program pengelolaan sampah tersebut. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitian deskriptif, teknik pengumpulan data menggunakan observasi wawancara, dan dokumentasi. Analisis data dilakukan dengan reduksi data, penyajian data, serta verifikasi dan penarikan kesimpulan. Hasil penelitian menunjukan bahwa strategi keberlanjutan program pengelolaan sampah dapat dilihat melalui penguatan kelembagaan lokal, membina kader masyarakat, dan sumber pendanaan. Sementara itu, pemberdayaan Kelompok Tani Lingkungan Hidup (KTLH) Sangga Buana dapat dilihat melalui keberlanjutan lingkungan, sosial, dan ekonomi. Strategi keberlanjutan program pengelolaan sampah sebagai pemberdayaan Kelompok Tani Lingkungan Hidup (KTLH) Sangga Buana dapat dikatakan berhasil, karena memiliki sumber pendanaan yang berkelanjutan, peningkatan kualitas lingkungan, serta menambah pendapatan anggota kelompok.Kata Kunci: Pemberdayaan, Kelompok Tani, Penegelolaan Sampah, Keberlanjutan